2017
DOI: 10.1038/s41598-017-06627-9
|View full text |Cite
|
Sign up to set email alerts
|

Primitive erythrocytes are generated from hemogenic endothelial cells

Abstract: Primitive erythroblasts are the first blood cells generated during embryonic hematopoiesis. Tracking their emergence both in vivo and in vitro has remained challenging due to the lack of specific cell surface markers. To selectively investigate primitive erythropoiesis, we have engineered a new transgenic embryonic stem (ES) cell line, where eGFP expression is driven by the regulatory sequences of the embryonic βH1 hemoglobin gene expressed specifically in primitive erythroid cells. Using this ES cell line, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 48 publications
(55 reference statements)
0
36
0
Order By: Relevance
“…Runx1 is expressed in all these sites of de novo blood cell emergence, as well as in all the hematopoietic cells, with the exception of mature erythrocytes (Lacaud et al, 2002;Lorsbach et al, 2004;North et al, 1999North et al, , 2002Sroczynska et al, 2009;Stefanska et al, 2017;Swiers et al, 2013;Zeigler et al, 2006). Disruption of Runx1 results in the complete absence of all hematopoietic cells other than primitive erythroid cells (Lacaud et al, 2002;Okuda et al, 1996;Wang et al, 1996).…”
Section: Embryonic Hematopoiesismentioning
confidence: 99%
“…Runx1 is expressed in all these sites of de novo blood cell emergence, as well as in all the hematopoietic cells, with the exception of mature erythrocytes (Lacaud et al, 2002;Lorsbach et al, 2004;North et al, 1999North et al, , 2002Sroczynska et al, 2009;Stefanska et al, 2017;Swiers et al, 2013;Zeigler et al, 2006). Disruption of Runx1 results in the complete absence of all hematopoietic cells other than primitive erythroid cells (Lacaud et al, 2002;Okuda et al, 1996;Wang et al, 1996).…”
Section: Embryonic Hematopoiesismentioning
confidence: 99%
“…The simultaneous appearance of blood and endothelial cells from a seemingly homogeneous cluster of mesodermal precursors initially led to the theory that primitive haematopoiesis did not originate from haemogenic endothelial cells (HECs), but from a developmentally earlier precursor termed haemangioblast, which displayed clonal bipotentiality for blood and endothelium and which had been detected in vitro [4] and in vivo [5]. More recent studies, however, have questioned the existence of such a bipotential precursor and have instead suggested that primitive blood may also derive from HECs located in the yolk sac [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…There, specialized endothelial cells, termed hemogenic endothelium (HE) based on their localization and simultaneous expression of endothelial and hematopoietic markers, trans-differentiate into hematopoietic cells by an endothelial-to-hematopoietic transition (EHT) ( Bertrand et al., 2010 , Boisset et al., 2010 , Kissa and Herbomel, 2010 , Taoudi et al., 2008 , Zovein et al., 2008 ). EHT has been shown to promote blood emergence not only in the embryo, but also in the extra-embryonic yolk sac (YS) ( Frame et al., 2016 ) and during in vitro differentiation of embryonic stem cells (ESCs) to blood ( Eilken et al., 2009 , Lancrin et al., 2010 , Stefanska et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…During these cultures, VE-cadherin (CDH5)-positive endothelial cells emerge and aggregate as endothelial cores. Within these cores, CDH5 + CD41 – HE cells, defined as HE1 ( Sroczynska et al., 2009a , Stefanska et al., 2017 ), further progress toward hematopoiesis by acquiring expression of the hematopoietic marker CD41. Spindle shaped CDH5 + CD41 + HE cells, defined as HE2, then start to round up and bud as hematopoietic cells from the cores.…”
Section: Introductionmentioning
confidence: 99%